GAMBARAN TINGKAT PENGETAHUAN TENAGA PELAKSANA ELIMINASI DALAM PELAKSANAAN PROGRAM PEMBERIAN OBAT PENCEGAHAN MASSAL (POPM) FILARIASIS (Studi di Wilayah Kerja Puskesmas Luwunggede, Kabupaten Brebes) - Larasati, Imeilda; Saraswati, Lintang Dian; Kusariana, Nissa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Lymphatic filariasis, commonly known as elephantiasis is an infectious disease caused by parasitic filarial worms that are transmitted by mosquitoes. The global program to control and eliminate lymphatic filariasis is Mass drug administration (MDA). Brebes Regency is one of the endemic areas of filariasis in Central Java Province. MDA program has been implemented from 2017 to 2021. However, the results have not reached the national target. The level of cadres knowledge about filariasis MDA in Luwunggede community health center has never been studied. The purpose of this study is to describe knowledge of cadres about MDA filariasis in the Luwunggede Health Care. This study used a cross-sectional study design and proportional random sampling as a sampling technique with a sample size of 80 respondents. The results showed that respondents who had high knowledge (52.5%) were almost the same as respondents who had low knowledge (47.5%). Increase cadres' knowledge about filariasis and filariasis MDA through training is needed.